Probing TBP interactions in transcription initiation and reinitiation with RNA aptamers that act in distinct modes - Fan, Xiaochun (National Academy of Sciences, 2004)
The TATA-binding protein (TBP) is a critical general transcription factor that associates with the core promoter and acts as a nexus for gene regulation through its interactions with other factors. A large number of proteins recognize the relatively small yet highly conserved C-terminal domain of TBP. One subset of these proteins (general transcription factors) interacts with the TBP·TATA complex and RNA polymerase II to create the preinitiation complex. To study TBP functions in preinitiation complex and other complexes, we generated a set of RNA aptamers with high affinity to yeast TBP. These aptamers act on TBP in different ways: all of them bind TBP competitively with DNA bearing the TATA element, and some can actively disrupt the TBP·TATA interaction in preformed, higher-order complexes containing the additional general transcription factors TFIIB and TFIIA. In crude cell extracts, the aptamers inhibit transcription in ways that reveal the dynamic nature of TBP interactions during initiation and reinitiation.